Kontribusi Mahasiswa Dalam Program MBKM Di RS.Prof.DR.Tabrani - Tiara Annisa Yosiana Harahap; Dian Puji Puspita Sari (Jurnal Pengabdian kepada Masyarakat Bina Darma, 2023)
With the existence of the MBKM program in the Health sector, one of which is in hospitals. Prof.Dr. Tabrani students gain experience in the world of work because a student is not only required to be competent in theoretical knowledge, but is also required to have soft skill competencies such as: Discipline, having a high work ethic, being able to communicate verbally and in writing, having a wide network, being able to take decisions, sensitive to the environment, and so on. The method used is direct implementation at the internship site. Activities during the internship include Closing payments for outpatient general patients, Closing payments for outpatient BPJS patients, Collecting clinical brobat patients, Recording the status of discharged patients, Closing BPJS discharge patients using the virtual client system, Making permission letters to go home from home Sick